COVID-19 Pandemic: An Insult Over Injury for Lebanon - Bizri, Abdul Rahman (J Community Health, 2020)
The outbreak of the novel coronavirus disease in 2019 (COVID-19) caused a plethora of challenges worldwide and tested healthcare systems across the six continents. Lebanon had recently faced harsh political and economic crises. We aim to describe the effect of COVID-19 on an already crisis-stricken country. A descriptive analysis of the burden of COVID-19 pandemic on Lebanon was performed. Relevant data on COVID-19 was retrieved from the Lebanese Ministry of Public Health from February 21 till June 13th, 2020. Results obtained were analyzed and a literature review was performed. 1422 confirmed COVID-19 cases were identified and reported in Lebanon by June 13th, 2020, comprising an incidence rate of 208/million persons. There has been a total of 31 deaths thus far, with a reported death rate of 5/million persons. The age group with the highest number of cases was 20–29 years. Beirut was the district with the highest number of cases (18%). The COVID-19 crisis has impacted the country on a multifactorial level. COVID-19 could not have come at a worse time for Lebanon. The country is on brink of bankruptcy, the healthcare system is struggling for survival and the government is striving to regain the trust of the population.